Prawne pojęcie rolniczej choroby zawodowej - SZEWCZYK, HELENA (Wydawnictwo Naukowe UAM, 2010)
In view of art. 12 of the Act of 20 December 1990 on social insurance for farmers, an occupational disease in agriculture is considered to be such a disease, which originated in relation with work on the farm, if the disease is included in the list of occupational diseases in the regulations issued based on the labour code. The concept of occupational disease in agriculture was thus constructed according to the restrictive list method, additionally supported by the determination of causes justifying the assumption of the occupational character of the disease, which significantly reduces the scope of protection granted to farmers suffering as a result of an agricultural occupational disease. The Author proposes to abandon the approach based on the closed list of occupational diseases. The basis for compensation should be extended to include the list of occupational diseases using the assumed causal effect between the occurrence of an occupational hazard and the incidence of the occupational disease. This would make it possible to include in the scope of the concept of occupational diseases in agriculture a considerable number of agriculture-related diseases, which at present do not have the status of occupational diseases.

Alla luce dell’art. 12 della legge 20 dicembre 1990 sulla previdenza sociale degli agricoltori per malattia professionale si intende una malattia che, sorta in seguito al lavoro svolto nell’azienda agricola, sia compresa nell’elenco di malattie professionali di cui alle disposizioni promulgate in base al codice del lavoro. La nozione di malattia professionale è stata costruita seguendo un metodo restrittivo. Le malettie professionali sono solo quelle comprese in un elenco, il quale fa riferimento solo alle cause che giustificano la qualificazione di una determinata malattia come professionale. Ciò limita notevolmente la tutela spettante agli agricoltori. L’Autrice auspica di scostarsi da questo metodo, che impiega un elenco non estendibile di malattie professionali. L’elenco dovrebbe essere ampliato fino a comprendere tutte le malattie per le quali sussiste un rapporto causale tra il rischio professionale e il sorgere della malattia professionale. Ciò consentirebbe di includere nella nozione di malattie professionali agricole una parte rilevante di malattie che, pur se collegate all’attività agricola, attualmente non hanno lo status di malattie professionali.